Exclusive breastfeeding and the impact of the NICU stay â a pilot prospective study - Sandra Soares Cardoso; Sara Catarino; Sara Geraldes Paulino; Filipa Flôr-de-Lima; Susana Pissarra; Sandra Costa (Portuguese Journal of Pediatrics)
Introduction and objectives: The World Health Organization aims for a prevalence of exclusive breastfeeding (EBF) at six months of ≥ 50%. Difficulties in EBF associated with Neonatal Intensive Care Unit (NICU) admission are documented, although with limited data in Portugal. The objective is to estimate the prevalence of EBF up to 6 months of age following NICU admission in the neonatal period and to evaluate factors related to EBF success. Methods: A prospective study was conducted on newborns admitted to a level III hospital NICU within the first 24 hours of life between October 2022 and January 2023. Data was collected by reviewing clinical records and interviews with caregivers during hospitalization and by telephone up to six months of age. Results: A total of 65 newborns were included with a mean gestational age of 35 weeks (SD ± 4) and a mean birth weight of 2411 g (SD ± 836). The primary reasons for hospitalization were prematurity (46%) and congenital anomalies (25%). At NICU discharge, 39% were under EBF. The prevalence of EBF was higher in newborns with a birth weight of < 1500 g (p = 0.025) and younger mothers (p = 0.020), but lower in cases of multiple pregnancies (p = 0.047). At two months of age, 29% maintained EBF, of which 53% were already on EBF at discharge. Up until six months of age, the prevalence of EBF was 14% while 29% continued with breastfeeding. Discussion: The prevalence of EBF at discharge was much lower than national data published regarding maternity unit discharge figures for healthy newborns. Determinants of EBF success were not identified and future studies with larger sample sizes are needed.